Papal overlordship and European princes, 1000-1270 - Wiedemann, Benedict ca. 20./21. Jh. (Oxford New York Oxford University Press, 2022)
This study reinterprets the relationship between the medieval papacy and independent states, suggesting that kings and governments were able to increase their effective power through close relationships with the international papacy, making the papacy integral to the creation of centralised national states and kingdoms in Europe.
Includes bibliographical references and index
Keywords: Popes -- Temporal power -- History -- To 1500; Kings and rulers, Medieval; Church and state -- Catholic Church -- History -- To 1500; Papacy -- History -- To 1309